Pembangunan Ekonomi Gereja: Suatu Kajian Praktis Pemberdayaan Ekonomi Jemaat Maranatha Bombon untuk Pelaksanaan Misi Gereja - Mardian Baali (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2023)
The natural wealth of the Maranatha Bombon Congregation, with various potentials, a gift from God, must be managed and cultivated with love so humans can use it to support their lives. God gave control as a delegation of guardianship or maintenance of nature for the welfare of human life, maintaining harmony with nature and glorifying God. Congregational economic empowerment can be realized through small holistic groups, which understand the Word through discussion, but also apply the Word to daily life and as a place to learn to serve others within and outside the group according to their gifts. The purpose of this research is to discover the reality of the life phenomenon of the GKLB Maranatha Bombon congregation towards financial independence that is relevant in the era of globalization. The research method used is qualitative. The results of this study indicate that economic empowerment has not been integrated into social and congregational life due to the lack of attention from the church itself.